Israeli settlements on Palestinian lands : socio-economic and political consequences - Jabarin, Sami M. I. (Kulliyyah of Islamic Revealed Knowledge and Human Sciencs,International Islamic University Malaysia, 2012)
This study examines the socio-economic and political consequences of Israeli settlements on Palestinian lands since 1967. The study focuses on Israeli policies in expropriated Palestinian lands and how these policies affected the socio-economic and political well-being of the Palestinians. It uses the settler colonialism as a framework for analysis. This study is qualitative in nature, using official documents and speeches of Palestinian and Israeli political leaders as sources of data. The study found that the Israeli settlements have affected the demography of Palestinian lands, the peace process, the right of self-determination of the Palestinians and the freedom of movement of the Palestinians. The study concludes that the two-state solution has failed and therefore Israelis and Palestinians should find a new framework to resolve the conflict. The framework should take into consideration the civil rights of the Palestinians.